2005
DOI: 10.1007/s10711-005-3087-x
|View full text |Cite
|
Sign up to set email alerts
|

A Diffeomorphism Classification of Generalized Witten Manifolds

Abstract: We give a classification of a specific family of seven-dimensional manifolds, the generalized Witten manifolds up to homeomorphism and diffeomorphism. Using an approach suggested by J. Shaneson, we develop a modified surgery theory which fully classifies these manifolds. In contrast to previous approaches, this surgery theory is designed to be more readily applicable to higher dimensions. The family contains examples of manifolds which admit Einstein metrics and are homeomorphic but not diffeomorphic. These pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…. , x [6,8,25] it has been shown that, already in dimension 7, there are infinitely many distinct homotopy types of such manifolds, distinguished by their cohomology rings.…”
Section: Maximal Effective Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…. , x [6,8,25] it has been shown that, already in dimension 7, there are infinitely many distinct homotopy types of such manifolds, distinguished by their cohomology rings.…”
Section: Maximal Effective Actionsmentioning
confidence: 99%
“…The fact that, in each dimension, there are only finitely many rational homotopy types of manifolds (S 5 × m i=1 S 3 )/S 1 and ( m i=1 S 3 )/T 2 is in stark contrast to the general situation. Indeed, in [6,8,25] it has been shown that, already in dimension 7, there are infinitely many distinct homotopy types of such manifolds, distinguished by their cohomology rings.…”
Section: Maximal Effective Actionsmentioning
confidence: 99%
“…where S 5 ⊂ C 3 , S 3 ⊂ C 2 , and k, l 1 , l 2 are nonzero integers such that k, l j are coprime for j = 1, 2; for such a space H 4 (M k,l1,l2 ) = Z l1l2 . We refer to [Esc05] for details.…”
Section: Theorem Bmentioning
confidence: 99%
“…Note that there are infinitely many manifolds in Theorems C and C that are not diffeomorphic to homogeneous spaces. Indeed, there are infinitely many spaces among Eschenburg and generalized Witten spaces that are not even homotopy equivalent to any homogeneous space [Sha02,Esc05].…”
Section: Theorem Bmentioning
confidence: 99%
“…(ii) Generalized Witten manifolds N kl are defined as the total spaces of fiber bundles with fiber the lens space L k (ℓ 2 , ℓ 2 ) and structure group S 1 . They have H 4 (N kl ; Z) ∼ = Z |ℓ1ℓ2| [34].…”
Section: Variations On Rational Fivebrane Classesmentioning
confidence: 99%